Relationship of Hand Sanitizer Usage Frequency with the Incidence of Irritant Contact Dermatitis during COVID-19 Pandemic - Almira Dwixie Dhara Desira; Puguh Riyanto; Liza Afriliana; Dea Amarilisa Adespin (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Irritant Contact Dermatitis (ICD) is an eruption of the skin caused by the non-immunologic inflammatory response of the skin to the irritant agents. The government urged to implement health protocols 3M, one of them is hand hygiene by used hand sanitizer to prevent the spread of COVID-19 infection. Repeated use of hand sanitizer can cause skin irritation and inflammatory response such as dryness, cracks, and other symptoms of ICD.Objective: To analyze the relationship between the frequency of use of hand sanitizer and the incidence of ICD.Methods: Observational analytics study cross-sectional design. The research subject were 260 medical faculty students of Diponegoro University who had to agree with informed consent, filled questionnaires and qualified by research criteria. Diagnostic of ICD based on questionnaires and physical examination of ICD. The statistical analysis data was used Chi-square test.Results: The results showed after analyze data use Chi-square test that there was not significantly related frequency use the hand sanitizer to the incidence irritant contact dermatitis during the COVID-19 pandemic with a p-value is 0,078 (p>0,05). The most frequent use of hand sanitizers is 5-10 times a day (56,5%), the most symptoms in ICD are dry, scaly, and peeling skin (30%), and the incidence of ICD due to the use of hand sanitizers are 33,5%.Conclusion: There was no significant relationship between frequency of use of hand sanitizer and irritant contact dermatitis during pandemic the COVID-19.